Eradicating Poverty and Unemployment: Narratives of Survivalist Entrepreneurs - Iwu, Chux Gervase; Opute, Abdullah Promise (Journal of Reviews on Global Economics, 2019)
Researchers continue to argue that survivalist entrepreneurs remain the untapped source for improved socioeconomic development because they have the potential to create employment, and reduce poverty. Unemployment and poverty remain the biggest challenges for sub-Saharan Africa but specifically South Africa with an escalating unemployment rate. This is the basis for this study, which set out to provide an authentic insight into the lives of survivalist entrepreneurs in Cape Town, South Africa, for the purpose of revealing the reasons why they are unable to significantly grow and add substantially to the economy. A qualitative approach by way of personal interviews was followed so as to gain an in-depth understanding of the participants' stories. The findings suggest that survivalist entrepreneurs are able to assist in the socioeconomic development of an economy if appropriate support is given to them by government or through some public-private growth initiatives. This study contributes to survivalist entrepreneurship literature by specifically illuminating why, according to Statistics South Africa, survivalist entrepreneurs do not seem to create more employment opportunities, improve the economy and alleviate poverty. In acknowledgment of some of the study's limitations, we consequently advise that further study in this area may consider a combination of methods as well as other locations.